2019
DOI: 10.2196/13039
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Geriatric Syndromes From Electronic Health Record Clinical Notes: Assessment of Statistical Natural Language Processing Methods

Abstract: Background Geriatric syndromes in older adults are associated with adverse outcomes. However, despite being reported in clinical notes, these syndromes are often poorly captured by diagnostic codes in the structured fields of electronic health records (EHRs) or administrative records. Objective We aim to automatically determine if a patient has any geriatric syndromes by mining the free text of associated EHR clinical notes. We assessed which statistical natural languag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 35 publications
(48 reference statements)
0
19
1
Order By: Relevance
“…In contrast, our figures were much lower than their findings of 16% for social connection/isolation using unstructured EHR data [13]. Another study revealed that 29.8% of their patients had a lack of social support documented in the EHR’s unstructured data [12,32]. Similar to previous studies [13], a small group of our patients had at least one note containing mentions of select SBDH domains; however, although these numbers were low, they were much higher than SBDH factors identified using EHR’s structured data.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…In contrast, our figures were much lower than their findings of 16% for social connection/isolation using unstructured EHR data [13]. Another study revealed that 29.8% of their patients had a lack of social support documented in the EHR’s unstructured data [12,32]. Similar to previous studies [13], a small group of our patients had at least one note containing mentions of select SBDH domains; however, although these numbers were low, they were much higher than SBDH factors identified using EHR’s structured data.…”
Section: Discussioncontrasting
confidence: 80%
“…Other domains, such as housing instability and poor social support, were reported for less than 1% of their patients. In another study, assessment of insurance claims and EHR data of older adults provided relatively similar results with only 0.03% of claims and 0.06% of EHR’s structured data providing information related to lack of social support [12,32]. Similarly, Torres et al [15] found SBDH codes being underutilized for tracking social needs using a national sample of hospital discharges (ie, <7% of discharges in any demographic or payer subgroup).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The expense and complexity of obtaining expert annotations of medical information is frequently cited as a major barrier to advancing machine learning-based technologies in medicine (67,68). While our approach did require expert-annotated data, we were able to achieve strong coding performance using a relatively small dataset of only 400 clinical documents, compared to the thousands of documents used in a recent study on extracting evidence of geriatric syndrome (28) or the tens of thousands used in foundational NLP research (69). Datasets of similar scale have been developed for automatic coding of other types of medical information (70), indicating that for a new type of health information, an initial dataset of a few hundred documents is likely to provide significant signal for machine learning.…”
Section: A Template For Expanding Automated Coding To New Concept Dommentioning
confidence: 94%